2019
DOI: 10.7759/cureus.5053
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Perceptions of the Doctor-Patient Relationship: A Cross-Sectional Study from Saudi Arabia

Abstract: Introduction The physician-patient relationship is at the heart of the art of medicine. Patient-centered care is rapidly evolving as the standard of care as well as the optimal vehicle to achieve high-quality healthcare and good clinical outcomes. This study aims to examine the attitudes of pre-clinical (third-year) students from Alfaisal University (Riyadh, Saudi Arabia) toward the physicianpatient relationship. Methods This cross-sectional study took place during the spring 2017 academic year. All third-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 8 publications
3
11
2
Order By: Relevance
“…The thematic evaluation found that 'Doctor-Patient Relations' with 18 publications was the second most studied domain. The synthesis of the included studies on medical ethics knowledge showed that most participants, mainly healthcare representatives had little knowledge about doctor-patient relations [ 32 , 33 , 36 , 41 , 42 , 44 , 45 , 48 ]. However, there was a strong consensus that every patient should be treated with honesty and dignity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thematic evaluation found that 'Doctor-Patient Relations' with 18 publications was the second most studied domain. The synthesis of the included studies on medical ethics knowledge showed that most participants, mainly healthcare representatives had little knowledge about doctor-patient relations [ 32 , 33 , 36 , 41 , 42 , 44 , 45 , 48 ]. However, there was a strong consensus that every patient should be treated with honesty and dignity.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a strong consensus that every patient should be treated with honesty and dignity. Patients of a high socioeconomic class should not be treated with extra care, and confidentiality should be maintained in all circumstances [ 32 , 33 , 36 , 41 , 42 , 44 , 45 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates and screening studies by title and abstract, 129 potentially eligible studies for inclusion were considered and their full text was retrieved. After full text screening, 49 studies [ 6 9 , 18 62 ] met the inclusion criteria and were included in the review with 20 studies ( n = 8050) [ 6 , 7 , 9 , 18 , 25 , 26 , 28 32 , 36 , 39 , 43 , 45 , 46 , 49 , 52 , 54 , 55 ] providing sufficient data for meta-analysis. Two studies were conducted using the same data set as other included studies therefore, we only used data from the original report in our meta-analysis [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, whether patients are recognized as having the ability to choose in medical decision-making reflects attitudes towards the "doctor/disease centred" or "patient-centred" medical service models. This attitude varies among different populations, according to previous research data [21,23,29,[37][38][39][40][41][42][43][44][45][46]. In more economically developed regions, both doctors and patients are more likely to develop a patient-centred attitude, while on the other hand, people in less developed areas are more likely to develop a doctor/disease-centred attitude.…”
Section: Discussionmentioning
confidence: 99%